Green–Light–Driven Poly(N-isopropylacrylamide-acrylamide)/Fe3O4 Nanocomposite Hydrogel Actuators - Cao, Ying; Li, Wenjiao; Quan, Fengyu; Xia, Yanzhi; Xiong, Zhong (Frontiers in Materials, 2022)
Light-responsive hydrogel actuators show attractive biomedical applications for in vivo drug delivery tool, surgical tissue repair operation, and vascular cleaning due to its non-contact, rapid, precise, and remote spatial control of light. Conventional visible–light–responsive hydrogels contain special chemical structure or groups, and the difficulty in synthesis results in that few can be applied to fabricate visible–light–driven hydrogel actuators. In this study, based on photothermal effect, surface-modified Fe3O4 nanoparticles were incorporated into poly(N-isopropylacrylamide-acrylamide) hydrogel by UV photopolymerization, which revealed excellent green–light–responsive volume change. Under a laser irradiation of 200 mW at 520 nm, the bending angle deformation of hydrogel strips with 2.62 wt% Fe3O4 reached 107.8°. Strip-shaped hydrogel actuators could be applied to transport tiny objects. Furthermore, a boomerang-like hydrogel actuator was designed and fabricated to drive floating foam on water. By 12 cycles of continuous laser on–off irradiation to a hydrogel actuator underwater, a circular returning movement of the float was accomplished. The study on driving a float using visible–light–triggered hydrogel actuators provides a new idea for the design of light-driven biomedical devices and soft robots.